Synthesis and Characterization of Silica-Biochar Composite as Rhodamine B Dye Adsorbent - Lisa Sari; Anis Shofiyani; Ajuk Sapar (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Composites are synthesized by combining different materials, resulting in properties suitable for use as adsorbents due to the combination of pores and functional groups within the constituent materials. This study developed a silica-biochar composite to serve as an adsorbent for rhodamine B dye, utilizing silica derived from red mud and biochar obtained from oil palm empty fruit bunches (OPEFB). This research focused on analyzing the characteristics and effectiveness of the composite as an adsorbent by varying its composition. Silica from red mud exhibited a purity of 80.05% and possessed silanol (Si-OH) and siloxane (Si-O-Si) functional groups on its surface, whereas biochar from OPEFB had a carbon content of 95.91% and included functional groups such as -OH, C=O, C=C, C-H, and C-O. The combination of silica and biochar yielded a composite surface consisting of -OH, C=O, C=C, C-O, C-H, and Si-O-Si functional groups. The silica-biochar composite demonstrated a greater surface area than its individual components, with silica at 69.824 m²/g and biochar at 95.452 m²/g. The composite with a 1:2 (% w/w) ratio exhibited the largest surface area at 102.371 m²/g, achieving a maximum adsorption capacity of 1.550 mg/g and an efficiency of 88.463%. The adsorption process encompasses physical interactions via pore diffusion and chemical interactions through functional groups.